(untitled) (Iranian Journal of Kidney Diseases, 2023)
Introduction. The prevalence of hyperuricemia shows an increasing trend among kidney transplant recipients. The association between metabolic syndrome and hyperuricemia among the recipients of kidney transplants may consequently lead to reduction in graft survival. In this regard, the present study aimed at comparing the kidney transplant recipients with and without metabolic syndrome in terms of the prevalence of hyperuricemia. Methods. This cross-sectional study was carried out on kidney transplant recipients who were referred to the Kidney Transplant Clinic of Montaserieh Organ Transplant Hospital, Mashhad University of Medical Sciences, from 2019 to 2020. The serum uric acid, anthropometric data, renal function, glucose levels, and lipid profile of the study participants were evaluated. Results. According to our findings, higher mean uric acid levels were reported in recipients with metabolic syndrome (6.9 ± 1.51 mg/dL), compared to recipients without metabolic syndrome (6.11 ± 1.47 mg/dL; P < .001). It was also found that 55.6 and 38.5% of the cases with and without metabolic syndrome had hyperuricemia, respectively (P < .05). Additionally, the results showed no significant association between hyperuricemia and the number of metabolic syndrome criteria (P > .05). A comparison between recipients with and without hyperuricemia revealed significantly lower levels of tacrolimus in the hyperuricemia group (P < .05). Regarding serum Tacrolimus levels, no significant difference was found between recipients with and without metabolic syndrome (P > .05). Moreover, there was no significant difference between recipients with and without hyperuricemia (P > .05) or metabolic syndrome (P > .05) in terms of serum cyclosporine level. Conclusion. The findings of the current study indicate that kidney transplant recipients suffering from metabolic syndrome have higher mean serum levels of uric acid than those without metabolic syndrome. DOI: 10.52547/ijkd.7141